Cardiovascular indicators at rest, and during an incremental test in young males - Eduardo Quieroti Rodrigues; Sergio de Sousa; Diego Giulliano Destro Christofaro; Mauro Leandro Cardoso; Robson Chacon Castoldi; Eduardo Zapaterra Campos; Pedro Balikian Junior; Ismael Forte Freitas Júnior (Revista Brasileira de Cineantropometria e Desempenho Humano, 2011)
The present study compared blood glucose levels, heart rate at rest and during exercise, besides body composition between hypertensive and normotensive individuals. The sample consisted of 32 young males with an average age of 22.6 years. Initially, the blood pressure was measured to split the sample into two groups: hypertensive and normotensive. Subsequently were measured, fasting blood glucose, bioelectrical impedance, anthropometry, and resting heart rate, heart rate during maximal effort test and recovery phase. Statistical analysis was composed by Student t test and two-way repeated measures analysis. The significance adopted was p = 0.05. The analyzed data showed that hypertensive patients present higher metabolic rates and hemodynamic values than normotensive individuals, which are indicators of cardiovascular risk.